Lubrication theory of ink hydrodynamics in the flexographic printing nip - Sauer, Hans Martin; Daume, Dominik; Dörsam, Edgar (Journal of Print and Media Technology Research, 2023)
On the base of hydrodynamical lubrication theory, we develop a mathematical model for the ink transfer in a flexographic printing process. When using the specific parameter ranges the model may also be applicable to the offset process. Specifically, we show how our model can be applied to viscous ink flows in the printing nip in presence of elastic printing plates, and how this sets limits to the possible resolution of the printing image. We also discuss the structure of the contact zone between printing plate and the substrate which is determined by the viscous and elastic stresses within the ink layer and the printing form. We also estimate the dynamic pressure profile in the ink during the transfer process. Finally, we discuss the phenomenon of ink seam formation at the rim of a flexographic printed pattern, and viscous finger formation. Explicitly, we show that important parameters, such as the width of an ink seam, the actual nip height, the size of the contact zone, and the ink shear, scale nonlinearly with printing speed. We derive the respective scaling exponents and compare the predictions with printing experiments.